2003
DOI: 10.1161/01.atv.0000051702.38086.c1
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Association Analysis Between Polymorphisms of PON Gene Cluster With Coronary Heart Disease in Chinese Han Population

Abstract: Objective-An extensive association analysis of PON gene cluster (PONs) with coronary heart disease (CHD) was performed in Chinese Han population. Methods and Results-Thirty polymorphisms of PON1, PON2, and PON3 gene were identified by direct sequencing of genomic DNA derived from 48 randomly selected patients. Twelve polymorphisms were additionally investigated for association with CHD in 474 male patients and 475 controls. Univariate analyses showed the cases had significantly higher frequencies of PON1 192Q … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
55
1
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(70 citation statements)
references
References 29 publications
(22 reference statements)
10
55
1
4
Order By: Relevance
“…The residents of this part of India, mostly Indo-Aryans, do not represent an ethnic homogeneity but do share common lifestyles and sociocultural heritage. The genotype prevalence in this group was in the order of CT > CC > TT, with C > T, this pattern being very similar to that reported for Japanese, Chinese, and Latino-American populations (Holland et al 2006;Yamada et al 2002;Wang et al 2003). This broad similarity in allele frequency and genotype distribution for the -108 polymorphism between different ethnic groups is quite unlike the wide variations seen between races for the PON1 gene's L55M and Q192R polymorphisms (Allebrandt et al 2002;Sanghera et al 1998;Garin et al 1997;Srinivasan et al 2004;Pati and Pati 1998;Agrawal et al 2009;Brophy et al 2001b).…”
Section: Discussionsupporting
confidence: 84%
“…The residents of this part of India, mostly Indo-Aryans, do not represent an ethnic homogeneity but do share common lifestyles and sociocultural heritage. The genotype prevalence in this group was in the order of CT > CC > TT, with C > T, this pattern being very similar to that reported for Japanese, Chinese, and Latino-American populations (Holland et al 2006;Yamada et al 2002;Wang et al 2003). This broad similarity in allele frequency and genotype distribution for the -108 polymorphism between different ethnic groups is quite unlike the wide variations seen between races for the PON1 gene's L55M and Q192R polymorphisms (Allebrandt et al 2002;Sanghera et al 1998;Garin et al 1997;Srinivasan et al 2004;Pati and Pati 1998;Agrawal et al 2009;Brophy et al 2001b).…”
Section: Discussionsupporting
confidence: 84%
“…PON1 directly form part of HDL particles whereas PON2 found in endothelial cells, smooth muscle cells and macrophages that possesses antioxidant properties similar to PON1 by delays cellular oxidative stress and prevents apoptosis in vascular endothelial cells 70,71 . Regarding three common polymorphisms in coding region of the human PON1 gene, the frequencies of Q192R, L55M, and C-108T for Taiwanese population were similar to those reported in the literature for the Chinese population 72,73 . Besides, we confirmed that paraoxonase, diazoxonase and arylesterase activities were directly influenced by the Q192R and C-108T polymorphisms.…”
Section: Discussionsupporting
confidence: 83%
“…However, differences in Q and R allele frequencies for the PON1 Q192R polymorphism between this population (Q = 0.71, R = 0.29) and Japanese population (Q = 0.40, R = 0.60) were observed, but were not found when compared with those of Caucasian populations (Q = 0.74, R = 0.26) (Zama et al 1997;Brophy et al 2001;Suehiro et al 2000). The very low frequency of the 55 M genotype in the Thai population was surprising, however, in a recent study of Han Chinese, no polymorphism of this site was found (Wang et al 2003), further investigations in this area are required. The allele frequencies for PON1 regulatory-region (T-108C and G-909C) polymorphisms also differed from those observed in both Japanese and Caucasian populations (Brophy et al 2001;Suehiro et al 2000;Leviev and James 2000).…”
Section: Discussionmentioning
confidence: 79%